2012
DOI: 10.5144/0256-4947.2012.603
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome components in obese Egyptian children

Abstract: BACKGROUND AND OBJECTIVESObesity is one of the most serious global health issues. The aim of this study was to assess the association between obesity and different components of metabolic syndrome among obese school children aged 7 to 9 years, and to identify associated clinical and biochemical characteristics.DESIGN AND SETTINGCase-control study among children attending Al-Zahraa Hospital Outpatient Clinic March 2010.SUBJECTS AND METHODSThe study included 60 obese children (28 boys and 32 girls) and 50 non-ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
(47 reference statements)
0
10
1
Order By: Relevance
“…In the present study the prevalence of MS in obese children was 36.2% which is higher than the Chinese, 24 Egyptian 25 and Turkish children, 13 but less than three other studies from Iran 26 , 27 and Turkey. 28 …”
Section: Discussioncontrasting
confidence: 72%
“…In the present study the prevalence of MS in obese children was 36.2% which is higher than the Chinese, 24 Egyptian 25 and Turkish children, 13 but less than three other studies from Iran 26 , 27 and Turkey. 28 …”
Section: Discussioncontrasting
confidence: 72%
“…49,51 The prevalence of MetS among obese children was reported to be more serious than that among normal weight children. 52 Metabolic syndrome was more common in Iranian obese children with a prevalence of 0.9% in normalweighed students, 11.3% in the overweight and 36.2% in the obese group, 53 which is higher than those reported in Chinese, 54 Egyptian, 55 and Turkish children 49 but less than another study from Turkey. 40 Moreover, the prevalence of MetS in overweight/obese French children aged 10-16 years old was 8.9%, 56 and that of Mexican children aged 6-12 years was 6.7%.…”
Section: Discussionmentioning
confidence: 74%
“…Obesity is one of the most serious risk factors for chronic diseases. It plays a central role in insulin resistance and metabolic syndrome [ 13 ]. Obese children in our study showed significant elevated serum insulin and insulin resistance (HOMA/IR) than controls.…”
Section: Discussionmentioning
confidence: 99%